Pulmonary Arterial Hypertension is Normalized Following Six Years of Inhaled Iloprost Treatment in a Patient with Systemic Sclerosis - Yoon, So-Young; Yoo, Eun-Soo; Yoo, Eun-Jung; Jung, Ju-Yang; Kim, Hyoun-Ah; Suh, Chang-Hee (Journal of rheumatic diseases, 2017)
Pulmonary arterial hypertension is a critical manifestation of systemic sclerosis (SSc) and is a main cause of death. Several treatment modalities for SSc have been identified, with effects that improve quality of life and mortality rates. However, whether these drugs can also normalize pulmonary arterial pressure, remains unclear. Here, we report the case of a woman with diffuse SSc with pulmonary arterial hypertension, who had a functional status equivalent to the New York Heart Association class III. The patient was treated with inhaled iloprost. After six years of inhaled iloprost therapy, echocardiography showed that pulmonary arterial pressure normalized, accompanied by improvement in functional capacity. Inhaled iloprost might not only normalize pulmonary arterial pressure, but also improve the functional status of patients with SSc with pulmonary arterial hypertension. (J Rheum Dis 2017;24:114-118) KCI Citation Count: 0